Comparison Study between Fraunhofer and Fresnel Diffraction in Case of Coherent and Incoherent Illumination - Hammadi, Hassan; A. AL-Ani, Ayad (Al-Nahrain Journal of Science, 2020)
In this paper, the effect of Coherent and Incoherent illumination in case of Fraunhofer and Fresnel diffraction have been studied. The comparison has been studied qualitatively in terms of Point Spread Function "PSF" and Modulation Transfer Function "MTF". This study assumed that there is no aberration and the medium is homogenous i.e.no turbulence. The results show that imaging in case of Fraunhofer diffraction pattern is better than imaging in case of Fresnel diffraction pattern, and for the two type of illumination. Moreover, imaging using incoherent illumination is better than imaging using coherent illumination, and for the two types of diffraction pattern